Enactivism in Autism Healthcare Practices: A Scoping Review. - van Huizen, Johannes Cornelis; Teunisse, Jan-Pieter; van Doormaal, Rosa H.; Orgassa, Antje; Staal, Wouter G.; Strijbos, Derek W. (Inquiry (00469580), 2026)
Introduction: Autism support needs can be viewed as 'wicked problems', underpinned by various disrupting factors distributed across time and space. This complexity strains care providers' ability to act swiftly and decisively. An integrative autopoietic-enactive approach may offer guidance by taking the individual's interactional social-ecological system as the central unit of analysis. In clinical practice and research, however, this approach is only beginning to take shape. A lack of definition and codification hinders practical guidance and clinical innovation. Method: To explore what autopoietic-enactive autism healthcare might mean in practice, this scoping review maps healthcare practices that are already based on autopoietic enactivism or bear affinity with it. Results: Forty-nine publications met with inclusion, representing 2.21% of the initial corpus. Findings were synthesized using four analytical lenses: aspects of (I) ecological-, (II) tangible-, (III), intersubjective-, and (IV) socio-cultural life, representing distinguishable albeit not separable dimensions of a person's social-ecological system. Conclusion: Our findings present a rich but still loosely integrated picture of healthcare practices. This scoping review provides a reference point from which the approach may be further defined and consolidated into a clinical research field. Plain Language Summary: Introduction: Supporting autistic people can be challenging because their needs are complex and evolve over time. This complexity makes it difficult for care providers to determine exactly what to do. One promising way forward is autopoietic enactivism, which looks at a person in relation to their environment. In clinical practice and research, however, an autopoietic-enactive approach is still new and not clearly defined. Method: To explore what autopoietic enactivism can bring to the clinical domain, we conducted a scoping review of autism healthcare practices that already use ideas from autopoietic enactivism. Results: Out of the full body of literature that we screened, 49 publications met our criteria. These findings were brought together using four different lenses that reflect different but connected parts of everyday life: aspects of (I) ecological-, (II) tangible-, (III), intersubjective-, and (IV) socio-cultural life – or, more precisely: the everyday life domains that people live in, the material things they interact with, the other people they interact with, and the wider social and cultural context that influences these interactions. Conclusion: Our findings provide a comprehensive overview of healthcare practices, but the overall picture is not yet fully coherent. By providing an overview of existing work, this scoping review can help turn autopoietic-enactive autism healthcare into a clearer, coherent, and more well-defined research field.